About Dichotomic Properties of Reason (from the history of European philosophical thinking) - O. Usalko (Oriental Studies, 2018)
The article analyzes the relationship between faith and reason, dichotomic properties of the reason. The author concludes that dichotomies to some extent are norms, and the study of these norms is indispensable from balanced understanding of the world of people and management of human life.